PERLINDUNGAN HUKUM ANAK DI LUAR PERKAWINAN DALAM PERSPEKTIF HAK PEMELIHARAAN (Lex Jurnalica, 2022)
Children out of wedlock do not have clear legal rules, even the Marriage Law and Constitutional Court Decision Number 46/PUU-VIII/2010 does not explain in detail the definition of children out of wedlock and the rights that must be obtained. So this study aims to analyze and describe the principle of justice against the limitation of children's rights outside of marriage and legal protection in obtaining maintenance and welfare rights. The research method used is normative juridical. The results of this study conclude that the legal vacuum of civil rights related to the maintenance and welfare of children outside of marriage is in fact not in accordance with the principle of justice, this is because the limitation of rights can harm the constitutional rights of children outside of marriage and legal protection of children outside of marriage by means of legal protection. preventive measures based on the Civil Code Article 867, Child Protection Law Article 7, Article 14, Article 21, Article 23 and Article 26, Child Welfare Law Article 2 paragraph (1) and Constitutional Court Decision Number 46 of 2010. voluntary and coercive as well as with court decisions based on considerations of the law governing the rights that must be obtained by children outside of marriage from their biological parents. Keywords: Legal Protection, Out of Wedlock Children, Right to Care